Comparative study between serum level of hepatocyte growth factor and CA-125 in patients with suspicious malignant adnexal masses - Ahmed, Ziad Mansour; Satar, Helmy Helmy Abdel; Zaki, Moyassar Ahmed; Hassan, Hassan Mansour (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Hepatocyte growth factor has been described to be increased in different cancers. The aim of the present study is to evaluate as a screening marker the‏ serum level of Hepatocyte growth factor among suspicious adnexal masses as compared to serum levels of CA125. Methods: The present study included 80 female patients who are admitted to the Gynecology unit in Elshatby Maternity University Hospital divided into two groups. Forty patients with benign gynecological conditions (control group) and 40 patients with suspicious malignant adnexal masses (cases group). Preoperative blood samples were withdrawn from all patients of both cases and control group to assess the level of serum hepatocyte growth factor (HGF) and serum cancer antigen 125 (CA 125). Both were quantified using ELISA technique. Results: Out of the 40 cases with suspicious malignant adnexal masses, 35 had ovarian cancer while five only were borderline. Patients with ovarian carcinomas had significantly higher preoperative HGF and CA 125 serum levels than patients with borderline pathology. Patients with borderline tumors had a significantly higher serum HGF and CA 125 levels than patients with benign gynecological conditions in control group. Conclusions: HGF in serum was elevated in 71% of patients with suspicious malignant adnexal masses proved to be ovarian cancer by histopathology using a quantitative ELISA. HGF can be used as a screening tool for ovarian cancer.